2020
DOI: 10.1007/s00268-020-05725-6
|View full text |Cite
|
Sign up to set email alerts
|

“First Do No Harm”: Significance of Delays from Diagnosis to Surgery in Patients with Non‐metastatic Breast Cancer

Abstract: Background The majority of patients with non-metastatic breast cancer will undergo surgery. This involves complex decisions that inevitably increase time from diagnosis to surgery beyond the currently recommended 30 days. This study aims to analyse factors that increase time to surgery and establish whether it is justifiable in the context of improved individualised breast cancer management. Methods A retrospective analysis of all patients at Austin Health surgically managed for non-metastatic invasive breast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…Like many others, we found that preoperative MRI was a significant factor in delaying TTS 5,6,11,12,17 and added an extra 12 days on average. Hulvat et al similarly found that the addition of MRI added an average of 11 days to TTS.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Like many others, we found that preoperative MRI was a significant factor in delaying TTS 5,6,11,12,17 and added an extra 12 days on average. Hulvat et al similarly found that the addition of MRI added an average of 11 days to TTS.…”
Section: Discussionsupporting
confidence: 83%
“…19 Our findings that patient age and race were not significant drivers influencing TTS are reassuring. These findings are mirrored by some, 6,10,12,16 but not by others. 4,5,7,20 We also found that tumor characteristics such as palpability, lymph node status, histologic subtype, and receptor profile had no impact on TTS.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations